2020
DOI: 10.1007/s10236-020-01404-1
|View full text |Cite|
|
Sign up to set email alerts
|

Sea-state contributions to sea-level variability in the European Seas

Abstract: The contribution of sea-state-induced processes to sea-level variability is investigated through ocean-wave coupled simulations. These experiments are performed with a high-resolution configuration of the Geestacht COAstal model SysTem (GCOAST), implemented in the Northeast Atlantic, the North Sea and the Baltic Sea which are considered as connected basins. The GCOAST system accounts for wave-ocean interactions and the ocean circulation relies on the NEMO (Nucleus for European Modelling of the Ocean) ocean mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…Waves can also contribute to extreme sea levels recorded by tide gauges, at hourly timescales, as already proposed by Charnock (1955); Stewart (1974). In fact, several studies have paid attention to this topic in recent years (Bertin et al, 2015;Melet et al, 2018;Bonaduce et al, 2020). The following wave-induced processes could affect sea level during a storm surge: (i) Stokes-Coriolis drift and consequent mass transport (Stokes, 1847;Hasselmann, 1970); (ii) wave induced effect on the wind stress, due to momentum exchange (Staneva et al, 2017); and (iii) wave setup (Longuet-Higgins and Stewart, 1962;Bowen et al, 1968).…”
Section: Introductionmentioning
confidence: 75%
“…Waves can also contribute to extreme sea levels recorded by tide gauges, at hourly timescales, as already proposed by Charnock (1955); Stewart (1974). In fact, several studies have paid attention to this topic in recent years (Bertin et al, 2015;Melet et al, 2018;Bonaduce et al, 2020). The following wave-induced processes could affect sea level during a storm surge: (i) Stokes-Coriolis drift and consequent mass transport (Stokes, 1847;Hasselmann, 1970); (ii) wave induced effect on the wind stress, due to momentum exchange (Staneva et al, 2017); and (iii) wave setup (Longuet-Higgins and Stewart, 1962;Bowen et al, 1968).…”
Section: Introductionmentioning
confidence: 75%
“…The IBI and NWS models offer the most complete coupling, while BAL and MED models only account for the Stokes Drift and the wave drag effects respectively and could therefore be limiting the water-level representation capabilities of these models. Several recent studies have reported on the significant impact of the wave coupling on water-levels around the European Northwest Shelf and Baltic regions, in particular during extreme events, which may increase coastal extreme sea-levels by several decimeters (Staneva et al, 2016;Staneva et al, 2017;Lewis et al, 2019;Bonaduce et al, 2020;Staneva et al, 2021).These studies argue that, on the shelf, the strongest impact is induced by the sea-state dependent sea-surface roughness, which can be importantly enhanced during growing, young sea states (Bertin et al, 2015, Pineau-Guillou et al, 2020. This process is currently lacking in the BAL model.…”
Section: Benchmarking and Model Configuration Impactsmentioning
confidence: 99%
“…For the experiments discussed later in this study, we use only the ocean circulation part based on the Nucleus for European Modelling of the Ocean (NEMO v3.6;Madec, 2017, Staneva et al, 2017, Bonaduce et al, 2020 with 3.5 km horizontal resolution as an ocean component of the Geesthacht Coupled cOAstal model SysTem (GCOAST). The NEMO setup used within the GCOAST system has an eddy-resolving spatial resolution of ∼3.5 km, and uses an explicit free-surface formulation (Madec 2017;Staneva et al 2021, Bonaduce et al, 2020. The model area covers the Baltic Sea, the Danish Straits, the North Sea and part of the northeast Atlantic Ocean.…”
Section: Observational and Model Datamentioning
confidence: 99%